Pre-treatment patient characteristics as predictors of drop-out and treatment outcome in individual and family therapy for adolescents and adults with anorexia nervosa: A systematic review and meta-analysis. (January 2019) - Gregertsen, Eva C.; Mandy, William; Kanakam, Natalie; Armstrong, Stephanie; Serpell, Lucy
Highlights: This meta-analysis summarised data on pre-treatment patient predictors of drop-out and treatment outcome in therapy for anorexia nervosa. Lower motivation and lower BMI at baseline, as well as having the binge-purge subtype of anorexia nervosa, predicted drop-out. Greater eating disorder pathology and lower motivation at baseline predicted poorer outcome. Future research incorporating carefully designed multi-site studies is required. Particularly, sufficiently large sample sizes are required so as to overcome the problem of insufficient power to detect differences. Abstract: Understanding variables predicting drop-out or unfavourable outcome following treatment for anorexia nervosa (AN) may help to improve upon intervention efforts. However, the current literature has demonstrated sparse and inconsistent significant findings. The current systematic review and meta-analysis summarised the evidence base examining baseline predictors of drop-out and outcome in AN treatment. A literature search was conducted to identify research investigating predictors of drop-out and outcome in individuals treated for AN. Four online databases were searched, and predictors were organised by category and dependent variable (outcome versus drop-out). 27 studies were included. Lower motivation, lower BMI, and having the binge-purge subtype of AN predicted drop-out. Greater ED pathology and poorer motivation predicted poorer outcome. Clinical recommendations include taking particular care during assessment stages to identify patients at risk of drop-out and/or poor outcome based on their clinical profile and level of motivation for recovery. At-risk patients should be receiving tailored treatment to enhance engagement and reduce risk of drop-out. In conclusion, there's some evidence that motivation, BMI, subtype, and ED pathology predicts drop-out and/or outcome in individual and family-based therapy for AN amongst adolescents and adults; however, research incorporating carefully designed multi-site studies is required to further examine these findings.